Adolescents' experiences of mentor alliance and sense of belonging in a site-based mentoring intervention. (July 2020) - Kazlauskaite, Vaida; Braughton, Jacqueline E.; Weiler, Lindsey M.; Haddock, Shelley; Henry, Kimberly L.; Lucas-Thompson, Rachel
Highlights: Youth mentor alliance and sense of belonging vary in site-based mentoring programs. Mentor insensitivity and communication difficulties linked to lower mentor alliance. Difficulty connecting with peers serves as a barrier to youth's sense of belonging. Mentor acceptance and empathy foster strong mentor alliance. Structure, positive norms, and supportive relationships bolster belonging. Abstract: Site-based youth mentoring programs provide a unique context for positive youth development. Conceptually, youth derive benefit not only from the mentor alliance (i.e., youths' feelings of compatibility with the mentor and satisfaction with the mentoring relationship), but also from their sense of belonging within the program. Using an exploratory sequential design, the purpose of this study was to illustrate the lived experiences of youth engaged in a site-based mentoring program. To draw distinctions in youths' experiences, we purposively sampled and interviewed 76 youth (ages 11–18; 60.5% male) in one of four subgroups based on self-reported survey data: high mentor alliance-high belonging, high mentor alliance-low belonging, low mentor alliance-high belonging, and low mentor alliance-low belonging. As anticipated, youth in the high mentor alliance-high belonging group described contributive experiences consistent with high-quality mentor characteristics (e.g., empathy, acceptance) and high-quality settings (e.g., positive social norms, support for efficacy and mattering). In contrast, youth in the low mentor alliance-low belonging group described mentors who were insensitive and noted difficulty connecting with peers. Difficulty connecting with peers was also a salient barrier for youth in the high mentor alliance-low belonging group. Finally, absent from the experiences of youth in the low mentor alliance-high belonging group was mentor empathy, acceptance, and authenticity. Our findings describe experiences that contribute to mentor alliance and sense of belonging in a site-based youth mentoring program, noting the challenge facing similar programs, which is to attend simultaneously to mentor and setting quality.